Implementing Agricultural Policies: Driving Sustainable Growth in the Farming Sector in Indonesia - Abdul Rahman (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The agricultural sector plays a crucial role in the economic development of Indonesia, providing employment opportunities and contributing to the country's food security. However, the sector faces numerous challenges that hinder its growth and sustainability. This research aims to explore the implementation of agricultural policies as a means to drive sustainable growth in the farming sector in Indonesia. The study's objective is to assess the effectiveness of agricultural policies in promoting sustainable practices, improving productivity, and enhancing the overall performance of the farming sector. The research employs a mixed-methods approach, combining qualitative and quantitative analysis. A comprehensive literature review is conducted to understand the existing agricultural policies and their impact on the sector. Primary data is collected through surveys and interviews with farmers, policymakers, and agricultural experts. The survey responses are analyzed using statistical techniques to identify trends, patterns, and correlations. The interviews provide insights into the perceptions and experiences of various stakeholders involved in the agricultural sector. The findings of this research shed light on the current state of agricultural policies in Indonesia and their impact on the farming sector. The analysis reveals the strengths and weaknesses of existing policies, highlighting areas that require improvement. Furthermore, the study identifies successful policy interventions and best practices that have contributed to sustainable growth in the farming sector. The study recommends policy measures to address the identified weaknesses and leverage successful interventions. By implementing effective agricultural policies, Indonesia can achieve sustainable growth in the farming sector, ensuring long-term economic prosperity and food security for its population.